Effect of starvation on Scylla serrata juveniles held in moist condition. - Lachica, Aileen N.
The effect of starvation on Syclla serrata juveniles held in moist condition was investigated in order to determine the survival of S. serrata juveniles subjected to starvation and to determine the survival of starved crabs after feeding in tanks. Two size-groups of crab juveniles in the intermolt stage were used; 0.0919 g for the small size group and 3.52 g for the big size group. Results showed that the big size group of S. serrata juveniles has a high percentage survival of 62 percent while the small size group has a low percent survival of only 5 percent. The median lethal time (LT50) for both the small and the big size group was between the 120th and 132nd hour (between days 5 and 6). At the end of the experiment the mortality of the small size group and big size group of juveniles was 95 percent and 38 percent respectively. Men weight loss among big size crb juveniles was larger than the small size crab juveniles. The SGR in both size groups is negative during starvation. The standard growth rate (SGR) was more negative among the big size group, implying a greater decrease in body weight (BW), carapace width (CW) and carapace length (CL) compared to the small size group. although the decrease in the body in CW and CL is minimal in both size groups compared to the decrease in the body weight. After refeeding of both the small and big size starved mud crab juveniles became positive indicating an increase in BW, CW, and CL. Increase however was greater among the big size group of mud crab juveniles than the small size group. The results obtained in this experiment can be used for the purpose of improving handling and holding technique during transport of mud crab S. serrata juveniles.